Effectiveness of policy on digital transformation in Kenya's national government : Huduma service delivery case study - Goga, Kevin, O. (My University, 2017)
“Flagship projects” is a hackneyed phrase that features prominently in Kenya’s government policy documents. Yet soon after their unveiling, some of these projects, notably ICT projects have stagnated or diverged from their core objectives as outlined in the said documents. Combining two established theoretical approaches, Hanna’s (2016a) digital transformation approach and McConnell’s (2010b) policy-as-a-programme framework, this study makes an original contribution to address the gap in literature and policy analysis, by tackling the complementarities in thinking about digital transformation as a programme and policy as a programme as it relates to Kenya’s Huduma citizen service experience. Employing a multi-method case study, including 20 key informant interviews, one 7-person focus group, observations at Nairobi’s City Square Huduma Centre and Huduma’s Network Operations Centre, and analysis of 18 policy documents relevant to this study, the research found that most digital innovation projects emphasised technology, while neglecting other key elements in the digital transformation space. However, the Huduma programme was different in that it paid due attention to several framework elements namely, policies and institutions, ICT infrastructure, ICT industry, human capital and public value, resulting into the category of resilient success. The analysis emphasises that sustainable digital transformation of public services can only be realised if all the transformational elements are prioritised in order to fit into the citizen’s way of life and integrate the Kenyan government’s “islands of automation”. The study makes a case for a “whole-ofgovernment” (WoG) digital transformation that extends beyond flagship projects. This will require creating and fostering collaborative leadership structures to enable digital transformation across national government ministries, departments and agencies, encouraged by youthful, highly-trained, non-political, professional leadership, and continuous learning in order to inculcate policy effectiveness and sustainability of digital transformation as a culture in all facets of national government. Key words: Digital transformation, effectiveness, policy, Huduma programme
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in the field of ICT Policy and Regulation to the Faculty of Humanities, University of the Witwatersrand, 2017
Keywords: Digital communications--Economic aspects--Kenya; Information technology